A new species of Nerice Walker, 1855 and further additions to the catalogue of Indian Notodontidae Stephens, 1829 (Lepidoptera: Noctuoidea) from Himalaya with report of range extensions - Mazumder, Arna; Raha, Angshuman; Sanyal, Abesh Kumar; Gayen, Subrata; Mallick, Kaushik; Bandyopadhyay, Uttaran; Chandra, Kailash; Schintlmeister, Alexander (Zootaxa, 2020)
The present work deals with the additional species of Notodontidae recorded from different provinces of Indian Himalaya subsequent to the publication of Catalogue of Indian Notodontidae which provided systematic account of 242 species and 10 subspecies. Current communication comprises: (I) Description of a new species of genus Nerice Walker, 1855, Nerice (Nerice) mishmiensis Mazumder, Raha, Chandra & Schintlmeister sp. nov., from Eastern Himalayan landscape of Dihang-Dibang Biosphere Reserve, Arunachal Pradesh, along with a comparative diagnosis with two other congeners viz. N. aemulator Schintlmeister & Fang, 2001 and N. upina Alphéraky, 1892; (II) Reporting of 3 species new to the Indian fauna from Eastern and Western Himalaya: Periergos genitale Schintlmeister, 2002, Honveda nepalina Nakamura, 1976 and Syntypistis nigribasalis tropica (Kiriakoff, 1974) with their diagnosis and genitalic illustrations; (III) Addition of 5 species and 1 more subspecies to the existing list from various literature; (IV) Additional distribution records of 40 species detected through primary sampling along with details of the materials examined; among which 3 species viz. Pseudallata laticostalis (Hampson, 1900), Baradesa lithosioides lithosioides Moore, 1883 and Ptilodon flavistigma (Moore, 1879) showed unusual altitudinal records around 3000 m. Thus, altogether Indian Notodontidae fauna has been updated to 247 species (including nominotypical subspecies) and 15 subspecies under 116 genera of 10 subfamilies.